(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There is no doubt FMCG marketers face unique challenges in tying marketing efforts to sales results. Unlike verticals as distinct as apparel, electronics, and financial services, FMCG product purchases still largely occur offline, where store placement and attractive product packaging matter as much – if not more – than advertising. Moreover, FMCG advertisers typically rely on third-party retailers like Tesco, Boots, and Costco to get their products to consumers. This means the retailer, not the FMCG manufacturer, owns the direct relationship with the customer and granular product purchase data that comes with it.In the end, while marketers in other verticals worry about the sophistication of their sales-based attribution models, FMCG marketers are still stuck measuring campaign success via proxies, such as demographic reach, viewability, and video completion rate. Consequently, marketing planning, execution, and optimisation are also based on proxies, rather than insight into what actually drove product sales.